2022
DOI: 10.1101/2022.02.07.479306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody Evasion Properties of SARS-CoV-2 Omicron Sublineages

Abstract: The identification of the Omicron variant (B.1.1.529.1 or BA.1) of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) in Botswana in November 20211 immediately raised alarms due to the sheer number of mutations in the spike glycoprotein that could lead to striking antibody evasion. We2 and others3-6 recently reported results in this Journal confirming such a concern. Continuing surveillance of Omicron evolution has since revealed the rise in prevalence of two sublineages, BA.1 with an R346K mutation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 20 publications
2
53
0
4
Order By: Relevance
“…3). A recent study using in vitro neutralization assays reported that there were differences in the reactivity of several mAbs against these different Omicron sublineages 38 . These observations suggest that BA.2 are antigenically distinct from BA.1 and BA.1.1, which is consistent with the data performed convalescent hamster sera 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). A recent study using in vitro neutralization assays reported that there were differences in the reactivity of several mAbs against these different Omicron sublineages 38 . These observations suggest that BA.2 are antigenically distinct from BA.1 and BA.1.1, which is consistent with the data performed convalescent hamster sera 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, S309 and REGN10987/REGN10933, which we previously showed were not effective against BA.1, reduced lung virus titers [mean reduction in viral titer = 2.7 and 2.2 log 10 (PFU/g), respectively], although the difference was not statistically signi cant between the REGN10987/REGN10933-and control mAb-treated groups. A recent study showed that the neutralizing activity of S309 against BA.2 is lower than that against BA.1 38 . The disparity between the in vitro and in vivo ndings may be due in part to the attenuated infectivity (~100fold lower levels) of BA.2 compared to BA.1 in hamster lungs (Fig.…”
Section: Ba2 and Ba1 Omicron Variants Show Similar Replication And Pa...mentioning
confidence: 97%
“…SASA was computed in PyRosetta using SasaCalc() and a 10 Å probe. The epitope accessibility score was then plotted versus the escape values measured in Liu et al 9 or Iketani et al 10 for each mutation using Seaborn regplot(). Note that the raw reported fold-change in IC 50 was first converted to fold-change relative to wild-type (IC 50,mutant /IC 50,WT ) and then the natural logarithm was taken prior to plotting.…”
Section: Methodsmentioning
confidence: 99%
“… Antibody epitope accessibility in RBD up versus RBD down correlates with observed S371L/F escape. Escape ( y-axis ) measured by Liu et al 9 and Iketani et al 10 against S371L, S371F, K417N, or E484A for 11 antibodies with solved crystal structures is plotted versus RBD down epitope accessibility ( x-axis ). Class 1–4 antibodies are annotated by color as shown in the legend at right.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation